Woman Violence in Afghanistan and The Return of Taliban in Contagious Violence Perspective - Valentia Nadya Dasadwiastaning (Politeknik Siber Cerdika Internasional, 2023)
This research shows that contagious violence is vital in spreading violence against women in Afghanistan. This research argues that it is vital to pay attention to how violence exposes a subject, when it happened and who, i.e. exposed to violence at that time. It is crucial also to produce immunity amidst a society in Afghanistan. It is crucial to prevent the broader transmission of violence in Afghanistan. Contagious violence and immunity theory show that Taliban is the Host of violence that needs to be overcome. Taliban were massively spreading violence to disrupt the immune system of anti-violence in Afghanistan. Hiding the proof and preventing report activity will cause horrible silent spreading of violence. This research also shows that tracing and immediate response to violent acts is needed to cut off the chain of contagious violence. Finding violence clusters and directly intervening is needed to prevent the subject who is already exposed from becoming more violent than the perpetrator. Producing an immunity system and direct intervention in all clusters of violence amidst society is more effective than urging the Taliban to stop the violence. Violence in Afghanistan is a contagious illness that has to be solved so a woman there can access their fundamental rights. Taliban can be categorized as one of